2005
DOI: 10.1088/0034-4885/68/3/r03
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear dynamics of semiconductor superlattices

Abstract: In the last decade, non-linear dynamical transport in semiconductor superlattices (SLs) has witnessed significant progress in theoretical descriptions as well as in experimentally observed non-linear phenomena. However, until now, a clear distinction between non-linear transport in strongly and weakly coupled SLs was missing, although it is necessary to provide a detailed description of the observed phenomena. In this review, strongly coupled SLs are described by spatially continuous equations and display self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
276
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(285 citation statements)
references
References 282 publications
(917 reference statements)
4
276
0
4
Order By: Relevance
“…Among the most typical physical objects, where the semidiscrete nonlinear systems find their applications are the semiconductor superlattices [10,26,34,51], electric superstructures [29], optical waveguide arrays [15], photonic crystal fibers [7] as well as the regular macromolecular structures of both natural [16] and synthetic [31] origin. The extensive bibliography on experimental realizations of discrete soliton-like entities is presented, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Among the most typical physical objects, where the semidiscrete nonlinear systems find their applications are the semiconductor superlattices [10,26,34,51], electric superstructures [29], optical waveguide arrays [15], photonic crystal fibers [7] as well as the regular macromolecular structures of both natural [16] and synthetic [31] origin. The extensive bibliography on experimental realizations of discrete soliton-like entities is presented, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…For small voltage values, electron transport chiefly involves the lowest miniband and there are many appropriate kinetic theory descriptions: semiclassical Boltzmann-type equations [1][2][3][4][5] , density matrix formulations 6,7 , transport equations for the nonequilibrium Green function (NGF) 8 , and Wigner-Poisson (WP) equations 9 . Semiclassical equations are easier to handle and, in particular, can be used to describe space-charge instabilities such as self-sustained oscillations of the current (SSOC) in dc voltage biased SLs due to the formation and dynamics of electric field domains 10 . SSOC can be found by deriving and solving a drift-diffusion system from the semiclassical kinetic equation 5 , or by a direct numerical solution of the latter 11 .…”
Section: Introductionmentioning
confidence: 99%
“…10 Recently, nonlinear dynamics involving electron transport in semiconductor superlattice driven by an intense terahertz electromagnetic irradiation has been a central focus of theoretical and experimental studies. [11][12][13][14][15][16][17][18] Keay et al 13 observed the photon-assisted tunneling and oscillatory dependence of the photon induced currents on terahertz electric field. It was reported that current through a biased GaAs/ AlAs superlattice is reduced when exposed to an intense terahertz field.…”
Section: Introductionmentioning
confidence: 99%